Evaluacion de dos cosechadoras de yuca - Leihner, D.E. (International Center for Tropical Agriculture, 1979)
Two trials were conducted to evaluate the efficiency of a commercial cassava harvester (A) and a harvesting implement (B): (1) the var. Chiroza (difficult, to harvest) was planted using 3 systems (beds, ridges and on the flat) at different densities and (2) three cassava var. (M Col 22, CMC 84 and M Mex 11) were planted on the flat. Harvester A left the roots totally exposed on the surface and partially removed the soil on them, while harvester B did not expose the roots totally. Root losses were greater than with manual harvesting and less than with harvester B; harvester A caused more root breakage. When comparing planting systems and densities, the proportion of roots left in the ground tended to be greater than in ridge planting at low densities and less than in cassava planted on the flat at a high density. The net working efficiency of harvester A was calculated at approx 0.2 ha/h, while that of harvester B was estimated at 0.5 ha/h. The overall damage for root breakage and bruising with harvester B was low, comparable to that of manual harvesting; that of harvester A being greater than. Harvester B was recommended for small farms while harvester A has potential for large-scale production. (CIAT)